Perbandingan Perhitungan Kebutuhan Irigasi Padi Metoda KP-01 dengan Cropwat-8.0 - I.D.S. Anggraeni; D.K. Kalsim (Jurnal Irigasi, 2013)
Two different methods for determining irrigation water requirement for paddy , i.e. KP-01 and CROPWAT-8.0, are assessed. The purpose of this research was to analyse paddy irrigation requirement based on KP-01 and CROPWAT-8.0 method. Those methods have different criterias to determine irrigation water requirement. That can be shown from parameters used such as reference crop evapotranspiration (ETo), effective rainfall, land preparation, crop coefficient and physical soil data. The average ETo value using KP-01 was higher (123.6%) than that using Penman-Monteith method (CROPWAT-8.0). The ratio of effective rainfall percentage KP-01 to CROPWAT-8.0 was 42.9%. Water requirement for land preparation using CROPWAT-8.0 was calculated from the water requirement during pre puddling and puddling, while KP-01 used a method developed by Van de Goor and Zijlstra. Water requirement for land preparation using CROPWAT-8.0 method was larger than that using KP-01. Paddy irrigation water requirement using CROPWAT-8.0 calculation was generally lower than that of KP-01, because the difference of effective rainfall method.